Supplier, tailor, and facilitator: Typology of platform business models - Junic Kim; Jihong Min (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
The platform business model is widely used because it is capable of various open innovation deliverables. However, it has a high probability of failure, caused by a variety of value streams that follow the two-sided market theory (each side has a distinct group of users). Therefore, extensive research on value streams and the attributes of platform business is essential to reduce platform business failure and ensure sustainable growth. By analyzing 21 case studies and conducting 30 in-depth interviews, this study proposes three types of Internet platform business strategies which can serve as a frame of reference to examine the impact of different value streams and open innovation on platform businesses. This study highlights a typology that sheds light on the heterogeneous meaning that corporates associated with creating new platform businesses adhere to and seeks to improve understanding of fundamental differences in platform business creation processes.
Keywords: 650; open innovation; platform; two-sided market; typology; value stream